Potential Application of Hydrocolloid-Based Oleogel and Beeswax Oleogel as Partial Substitutes of Solid Fat in Margarine - Khadije Abdolmaleki; Leyla Alizadeh; Kooshan Nayebzadeh; Hanna Maria Baranowska; Przemysław Łukasz Kowalczewski; Amin Mousavi Khaneghah (Applied Sciences, 2022)
The purpose of this study was to produce margarine with reduced trans and saturated fatty acid contents using 10% beeswax oleogel and hydrocolloid-based oleogel containing 3.15% sodium caseinate, 0.5% guar gum, and 0.22% xanthan gum with a melting point, rheological and textural characteristics similar to palm oil. Oleogel samples were used as a substitute for palm oil and partially hydrogenated palm olein oil. Margarine (70% fat) formulated with these oleogels was investigated for solid fat content (SFC), melting point, and rheological and textural properties. The results showed that the replacement of 100% partially hydrogenated palm olein oil (PHPO) and 25% palm oil (PO) with beeswax oleogel and the replacement of 100% PHPO with hydrocolloid-based oleogel resulted in the production of margarine with rheological and textural properties similar to the commercial control margarine. In addition, these samples had a lower content of SFC and a higher melting point than the commercial control sample. The amounts of saturated and trans fatty acids also decreased. These were 28% and 80% in the sample containing beeswax and 15% and 73% in the sample with hydrocolloid-based oleogels for saturated and trans fatty acids, respectively. It was concluded that it is possible to manufacture margarine using the oleogel method while maintaining its physical characteristics and improving its nutritional properties.